AIAA Atmospheric Flight Mechanics Conference 2012
DOI: 10.2514/6.2012-4644
|View full text |Cite
|
Sign up to set email alerts
|

Model-based aerodynamic-angle attitude control of an atmospheric entry capsule

Abstract: The paper describes the attitude control system of a low lift-to-drag biconic atmospheric entry capsule based on the Embedded Model Control methodology. The control structure derives from the development of the attitude dynamics and kinematics written in terms of aerodynamic angles, instead of Euler/quaternion kinematics. A detailed development of the simplified set of equations linking the torques generated by the reaction control system with the time evolution of the aerodynamic angles is provided. The simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The time evolution of the tracking law, combined with the path-planning algorithm and the attitude control in Canuto et al 25 is shown below assuming a 10 % dispersion of the drag aerodynamic coefficient. This should be a worst-case condition since 10 % corresponds to the 3 dispersion of the capsule aerodynamic database.…”
Section: A 10 % Error Of the Drag Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The time evolution of the tracking law, combined with the path-planning algorithm and the attitude control in Canuto et al 25 is shown below assuming a 10 % dispersion of the drag aerodynamic coefficient. This should be a worst-case condition since 10 % corresponds to the 3 dispersion of the capsule aerodynamic database.…”
Section: A 10 % Error Of the Drag Coefficientmentioning
confidence: 99%
“…The paper provides a description of the selected solution for the path planning and reference-path tracking algorithms, and the output of a simulation campaign using a high-fidelity 6 degrees-of-freedom simulator. The attitude control, in charge of actuating a reaction control system for regulating the vehicle bank angle is described by the same authors in 25 . A preliminary description of the selected solution can be found in 26 .…”
mentioning
confidence: 99%